Tyrosine-phosphorylated SOCS3 negatively regulates cellular transformation mediated by the myeloproliferative neoplasm-associated JAK2 V617F mutant. (November 2019) - Funakoshi-Tago, Megumi; Tsuruya, Rina; Ueda, Fumihito; Ishihara, Aki; Kasahara, Tadashi; Tamura, Hiroomi; Tago, Kenji
Graphical abstract: Highlights: SOCS3 induces the degradation of the JAK2 V617F mutant. SOCS3 inhibits tumorigenesis induced by the JAK2 V617F mutant. The phosphorylation of SOCS3 may be essential for its inhibitory effects. Abstract: In the majority of myeloproliferative neoplasms (MPNs) patients, a point mutation, V617F has been found in Janus kinase 2 (JAK2) gene, and this JAK2 mutant provoked aberrant signaling pathway. In the current study, we found that suppressor of cytokine signaling proteins 3 (SOCS3) possessed the tumor suppressive activity against the JAK2 V617F mutant-provoked cellular transformation. The knockdown of SOCS3 increased the expression level of the JAK2 V617F mutant, which enhanced the activation of signaling mediators, including signal transducer and activator of transcription 3 and 5 (STAT3, STAT5) and extracellular signal-regulated kinase (ERK), and also increased of the proliferation rate and tumorigenesis activity of Ba/F3 cells expressing the JAK2 V617F mutant and erythropoietin receptor (EpoR). In contrast, the enforced expression of SOCS3 significantly inhibited the JAK2 V617F mutant-induced activation of downstream signaling molecules, cell proliferation, and tumorigenesis by down-regulating the expression level of the JAK2 V617F mutant. SOCS3 interacted with the JAK2V617F mutant through its SH2 domain and was phosphorylated at Tyr-204 and Tyr-221 in its SOCS box by the JAK2V617F mutant. SOCS3 mutants carrying a mutation in the SH2 domain (R71E) and a substitution at Tyr-221 (Y221F) failed to exert inhibitory effects on JAK2V617F mutant-induced cellular transformation and tumorigenesis. Collectively, these results imply that SOCS3 plays a negative role in the JAK2 V617F mutant-induced oncogenic signaling pathway through its SH2 domain and the phosphorylation of Tyr-221 in its SOCS box.